BIOGAS PRODUCTION TECHNOLOGY - Aliyev Suxrob Rayimjonovich,; G'anijonova Shaxlo Sherzodbek qizi, (Лучшие интеллектуальные исследования, 2024)
Abstract: Biogas, a versatile fuel derived from organic waste, presents a promising solution to mitigate greenhouse gas emissions while generating clean energy. To harness its full potential, here are five innovative technologies driving the evolution of biogas extraction: